Pengaruh Variabel Moderasi Kelembagaan terhadap Hubungan Modal Sosial dan Kinerja Usahatani Kapulaga di Lahan Perhutani Kabupaten Banyumas - Yuli Fatiah; Hernowo (Program Studi Agribisnis INSTIPER Yogyakarta, 2023)
The cardamom land area of Banyumas Regency is the second largest in Central Java Province, which is 322.5 hectares. Social capital is an important factor to open networks between agricultural actors and other interested parties. The goal of this research is to know about: (1) the characteristics of social and organization capital of cardamom ranchers in forestry land in Banyumas Regency; (2) the coordinate impact of social and organization capital on the execution of cardamom farmers' cultivating in forestry land in Banyumas Regency; and (3) knowing whether organization factors are control factors in coordinate relations between social capital and the performance of cardamom farming in the forestry land of Banyumas Regency. The target of the study was farmers who carried out cardamom farming on Perhutani land in purposively selected locations, namely Kedungbanteng, Pekuncen and Gumelar Districts, Banyumas Regency. The three sub-districts are cardamom farming centers on forestry land in Banyumas Regency. The results showed that the characteristics of social and institutional capital at the study site on average had a high category. The cardamom farming business carried out is already profitable and worthy of development. The SEM-PLS analysis shows that the most dominant indicator measuring social capital is trust, while the most dominant indicator measuring institutionality is cultural value. Furthermore, social and institutional capital directly affects the performance of cardamom farming, but institutions cannot be a moderation variable of the social capital variable to the performance of farming.